A Comparative Review of Methods of Using Soil Colors and their Patterns for Wetland Ecology and Management. Issue 11 (17th June 2019) - Schmidt, Stephanie A.; Ahn, Changwoo
ABSTRACT: Soil color patterns are essential to understand hydrologic regime and biogeochemical processes in wetland ecosystems. Munsell Soil Color Chart (MSCC) has been traditionally and predominantly used to identify and quantify hydric soil field indicators, but several simple, low-cost alternatives have become recently available to compare their efficacy in complementing the MSCC in soil color assessment. We conducted an intensive literature review on studies utilizing different methods to identify and quantify hydric soil colors and associated patterns; these include 1) the MSCC, 2) the Nix Color Sensor, 3) mobile phone camera (MPC) and medium-end digital camera photography, and 4) colorimetry and spectrometry. A review of these methods elucidates their respective strengths and weaknesses and highlights the importance of considering study-specific attributes in determining which method to choose for field studies of hydric soil colors. Redoximorphic features (RMFs) require methods capable of capturing small and heterogeneous soil surfaces and features such that the MSCC and digital photography are the most appropriate methods; on the other hand, the Nix Color Sensor provides rapid assessment of soil color that does not necessitate rigorous training to overcome biases that might come about in more subjective methods such as the MSCC. Overall, all alternative methods reviewed have their own merits and capacity to complement measurements made by the MSCC.